Antimicrobial Resistance Profiles of Coagulase-Negative Staphylococci in Community-Based Healthy Individuals in Germany - Marincola, Gabriella; Liong, Olivia; Schoen, Christoph; Abouelfetouh, Alaa; Hamdy, Aisha; Wencker, Freya D. R.; Marciniak, Tessa; Becker, Karsten; Köck, Robin; Ziebuhr, Wilma (Frontiers in Public Health, 2021)
Coagulase-negative staphylococci (CoNS) are common opportunistic pathogens, but also ubiquitous human and animal commensals. Infection-associated CoNS from healthcare environments are typically characterized by pronounced antimicrobial resistance (AMR) including both methicillin- and multidrug-resistant isolates. Less is known about AMR patterns of CoNS colonizing the general population. Here we report on AMR in commensal CoNS recovered from 117 non-hospitalized volunteers in a region of Germany with a high livestock density. Among the 69 individuals colonized with CoNS, 29 had reported contacts to either companion or farm animals. CoNS were selectively cultivated from nasal swabs, followed by species definition by 16S rDNA sequencing and routine antibiotic susceptibility testing. Isolates displaying phenotypic AMR were further tested by PCR for presence of selected AMR genes. A total of 127 CoNS were isolated and Staphylococcus epidermidis (75%) was the most common CoNS species identified. Nine isolates (7%) were methicillin-resistant (MR) and carried the mecA gene, with seven individuals (10%) being colonized by at least one MR-CoNS isolate. While resistance against gentamicin, phenicols and spectinomycin was rare, high resistance rates were found against tetracycline (39%), erythromycin (33%) and fusidic acid (24%). In the majority of isolates, phenotypic resistance could be associated with corresponding AMR gene detection. Multidrug-resistance (MDR) was observed in 23% (29/ 127) of the isolates, with 33% (23/ 69) of the individuals being colonized by MDR-CoNS. The combined data suggest that MR- and MDR-CoNS are widespread in the community, with previous animal contact not significantly influencing the risk of becoming colonized by such isolates.